Actinobacillus actinomycetemcomitans Keratitis After Glaucoma Infiltration Surgery: A Clinical Report and Literature Review. Issue 3 (January 2016) - Hong, Jiaxu; Xu, Jianjiang; Cao, Wenjun; Ji, Jian; Sun, Xinghuai
Abstract : Abstract: Actinobacillus actinomycetemcomitans infection is a rare and easily misdiagnosed ocular disease. In this article, the authors report a chronic, purulent, and difficult-to-treat case of A actinomycetemcomitans keratitis following a glaucoma infiltration surgery. A 56-year-old man with a long-standing history of open-angle glaucoma in both eyes presented with a 12-week history of ocular pain, redness, and blurred vision in his right eye. He underwent a glaucoma infiltration surgery in his right eye 6 months ago. Three months postoperatively, he developed peripheral corneal stromal opacities associated with a white, thin, cystic bleb, and conjunctival injection. These opacities grew despite topical treatment with topical tobramycin, levofloxacin, natamycin, amikacin, and metronidazole eye drops. Multiple corneal scrapings revealed no organisms, and no organisms grew on aerobic, anaerobic, fungal, or mycobacterial cultures. The patient's right eye developed a severe purulent corneal ulcer with a dense hypopyon and required a corneal transplantation. Histopathologic analysis and 16S ribosomalribonucleic acid polymerase chain reaction sequencing revealed A actinomycetemcomitans as the causative organism. Postoperatively, treatment was initiated with topical levofloxacin and cyclosporine, as well as oral levofloxacin and cyclosporine. Graft and host corneal transparency were maintained at the checkup 1 month after surgery. Although it is a rare cause of corneal disease, A actinomycetemcomitans should be suspected in patients with keratitis refractory to topical antibiotic therapy. Delay in diagnosis and appropriate treatment can result in vision loss.